Atomic Origins of Enhanced Ferroelectricity in Nanocolumnar PbTiO3/PbO Composite Thin Films. Issue 12 (2nd January 2023) - Li, Mengsha; Chen, Pingfan; Zhang, Yingli; Zhang, Yuan; Liu, Zhenghao; Tang, Chunhua; Chung, Jing Yang; Gu, Mingqiang; Li, Junxue; Huang, Zhen; Chow, Gan Moog; Li, Changjian; et al.
Abstract: Nanocomposite films hold great promise for multifunctional devices by integrating different functionalities within a single film. The microstructure of the precipitate/secondary phase is an essential element in designing composites' properties. The interphase strain between the matrix and secondary phase is responsible for strain‐mediated functionalities, such as magnetoelectric coupling and ferroelectricity. However, a quantitative microstructure‐dependent interphase strain characterization has been scarcely studied. Here, it is demonstrated that the PbTiO3 (PTO)/PbO composite system can be prepared in nano‐spherical and nanocolumnar configurations by tuning the misfit strain, confirmed by a three‐dimensional reconstructive microscopy technique. With the atomic resolution quantitative microscopy with a depth resolution of a few nanometers, it is discovered that the strained region in PTO is much larger and more uniform in nanocolumnar compared to nano‐spherical composites, resulting in much enhanced ferroelectric properties. The interphase strain between PbO and PTO in the nanocolumnar structure leads to a giant c/a ratio of 1.20 (bulk value of 1.06), accompanied by a Ti polarization displacement of 0.48 Å and an effective ferroelectric polarization of 241.7 µC cm −2, three times compared to the bulk value. The quantitative atomic‐scale strain and polarization analysis on the interphase strain provides an important guideline for designing ferroelectric nanocomposites. Abstract : Nanocomposite films provide a general strategy for enhancing functionalities, but the atomic scale evidence is missing. By using PbTiO3 /PbO as a prototypical system, an atomic‐scale quantitative analysis of the strain and polar displacement reveals that the nanocolumnar composite configuration is critical to impose a uniform vertical straining effect, resulting in much enhanced ferroelectric properties in composite thin films.